SOURCES OF FINANCE AND FINANCIAL PERFORMANCE OF FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
Financing of business operations is a critical requirement for the success of any business venture and thus is fundamental to the achievement of the corporate objectives of any establishments. Finance is the management of the flows of money through an organization. Such flows include outflows and inflows of financial resources. In order to implement an investment decision, the necessary finance (capital) must be acquired. There are three methods of financing business operations and they are: borrowing (debt), issuing equity (stock ownership), and internal funding. To make decisions on the financing of the organization, the manager needs to know the cost of the various sources of finance at his disposal in order that he may select the most efficient funding package. The study aimed to identify the various sources of finance to an organization. The objective of this study is to review extant literature on the various sources of finance to an organization in Nigeria. The methodology adopted for this study is library approach which focuses on content review of extant literature. We concluded that firms depend more on formal banking sources for investment and that management and Board of Directors should pay attention to the utilization of these sources particularly short-term finance to avoid mismatch. We recommended that managers should know the cost of various sources of finance and use fund, which will reduce cost of capital. Also, companies should use more of debt financing because it is less risky and costly compared to capital market source.
Keywords: Borrowing; Finance; Internal Funding; Issuing Equity; Sources of Finance